Analisis Koreksi Fiskal Atas Biaya dan Penghasilan Terhadap PPH Terutang PT. Ahza Rizqi Barokah: Studi Kasus PT. Ahza Rizqi Barokah - Dina Triani; Reza Praditya (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
The purpose of this research is to determine the amount or amount of income tax payable by PT. AHZA RIZQI BAROKAH by re-analyzing the fiscal corrections to income and expenses that have been made by the company based on tax laws and regulations. In this study, it will be explained and explained that there are differences in the recognition of income and expenses in commercial and fiscal accounting, as well as the calculation of corporate income tax payable. This research uses descriptive method with qualitative and quantitative approaches. A qualitative approach is used to analyze the data under study based on tax laws and regulations, while a quantitative approach is used to analyze the data under study by calculating to answer the problem formulation. The results of the analysis from the research conducted by the author show that based on the results of the author's research, before the fiscal correction was carried out, the costs recorded in the commercial financial reports were Rp.884,546,137,- and after the fiscal correction was carried out the costs were Rp.882,373,353, - due to the cost of fiscal reports which are smaller than commercial reports, causing the income tax payable to be greater. based on the results of the author's research before the income tax correction was carried out which was recorded in the commercial financial statements of Rp. -26,272, - and after the income tax correction was carried out to Rp. -354,351, - due to the income tax report being smaller than the commercial report causing the income tax payable to be smaller. pph payable before a fiscal correction of Rp. 6,772,000, - and after the fiscal correction of the income tax payable became Rp. 6,975,000, - meaning that the effect that occurred on PT Ahza Rizqi Barokah after the fiscal correction of the income tax payable became bigger.